Improved Hybrid Exponentially Weighted Moving Average Control Chart using Auxiliary Information - Tariq, Sadia; Noor-ul-Amin, Muhammad; Hanif, Muhammad; Jun, Chi-Hyuck (Journal of Reliability and Statistical Studies, 2020)
Statistical process control is an important tool for maintaining the quality of a production process. Several control charts are available to monitor changes in process parameters. In this study, a control chart for the process mean is proposed. For this purpose, an auxiliary variable is used in the form of a regression estimator under the configuration of the hybrid exponentially weighted moving average (HEWMA) control chart. The proposed chart is evaluated by conducting a simulation study. The results showed that the proposed chart is sensitive with respect to the HEWMA chart. A real-life application is also presented to demonstrate the performance of the proposed control chart.